2006
DOI: 10.1111/j.1467-9612.2006.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

The crosslinguistic syntax of sluicing: evidence from hungarian relatives

Abstract: Abstract.  This paper deals with an elliptical construction in Hungarian that to our knowledge has not received any attention in the theoretical literature so far. It involves the deletion of a relative clause with the exclusion of the relative pronoun and one more remaining constituent. We show that this construction should be analyzed as an instance of sluicing. The theoretical approach we provide for these sentences is an adapted version of Merchant's (2001) implementation of sluicing in terms of an [e]‐fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In Gungbe, wh-and focus elements move to the same 6 In more exact detail the authors suggest that sluicing tracks wh-syntax in languages: the feature content of whelements in non-elliptical questions determines what kind of remnants can escape TP-ellipsis in sluicing. In an E-feature approach like Merchant's (2001), this boils down to the licensing requirement making reference to features on the remnant relativized to the type of features found on interrogatives, as stated in (i) (i) THE WH/SLUICING-CORRELATION (van Craenenbroeck and Lipták 2006) The syntactic features that the E-feature checks in a certain language are identical to the strong features a whphrase checks in a non-elliptical constituent question in that language. …”
Section: Syntactic Licensingmentioning
confidence: 99%
See 3 more Smart Citations
“…In Gungbe, wh-and focus elements move to the same 6 In more exact detail the authors suggest that sluicing tracks wh-syntax in languages: the feature content of whelements in non-elliptical questions determines what kind of remnants can escape TP-ellipsis in sluicing. In an E-feature approach like Merchant's (2001), this boils down to the licensing requirement making reference to features on the remnant relativized to the type of features found on interrogatives, as stated in (i) (i) THE WH/SLUICING-CORRELATION (van Craenenbroeck and Lipták 2006) The syntactic features that the E-feature checks in a certain language are identical to the strong features a whphrase checks in a non-elliptical constituent question in that language. …”
Section: Syntactic Licensingmentioning
confidence: 99%
“…For Hungarian specifically, van Craenenbroeck and Lipták (2006) have shown that sluicing can leave any operator phrase in the left periphery, not only wh-or focus-constituents but also (universal) quantifiers.…”
Section: Syntactic Licensingmentioning
confidence: 99%
See 2 more Smart Citations
“…I submit that the reason why nem is different from igen in this respect has to do with the fact that negation, unlike affirmative polarity, is a logical operator. As van Craenenbroeck and Lipták (2006) Leaving igen's intimate relationship with contrast for future investigation, its dependency on elliptical contexts can be given the following account. Since igen cannot be the spell-out of the elliptical site as a whole according to the extraction test applied above (cf.…”
mentioning
confidence: 99%